Association between Molecular Mechanisms and Tooth Eruption in Children with Obesity - Carla Traver; Lucía Miralles; Jorge Miguel Barcia (MDPI AG, 2022)
Different works have reported earlier permanent teething in obese/overweight children compared to control ones. In contrast, others have reported a delayed permanent teething in undernutrition/underweight children compared to control one. It has been reported that becoming overweight or suffering from obesity can increase gingival pro-inflammatory drive and can affect orthodontic treatment (among other complications). In this sense, little is known about the molecular mechanisms affecting dental eruption timing. Leptin and adiponectin are adipocytokines signaling molecules released in overweight and underweight conditions, respectively. These adipocytokines can modulate osteocyte, odontoblast, and cementoblast activity, even regulating dental lamina initiation. The present review focuses on the molecular approach wherein leptin and adiponectin act as modulators of Runt-related transcription factor 2 (Runx 2) gene regulating dental eruption timing.